MODEL OF EFFICIENCY IMPROVEMENT ON ACADEMIC JOURNAL MANAGEMENT OF FACULTY OF HUMANITIES AND SOCIAL SCIENCES, PHRANAKHON RAJABHAT UNIVERSITY - Maneemai, Suppachock (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
This research aimed to 1) study problems in academic journal management of the Faculty of Humanities and Social Sciences in the aspect of factors contributing to the efficiency improvement of the journal, and 2) suggest a model of efficiency improvement in academic journal management of the Faculty of Humanities and Social Sciences using the PAM-POSDCoRB conceptual framework. The scope of this study consisted of 105 lecturers from the Faculty of Humanities and Social Sciences. The number of respondents to the questionnaire was 58, representing 48.3 percent. The findings revealed that: 1) The management problems of the academic journal of the Faculty of Humanities and Social Sciences were mainly not found in terms of management but had a moderate level due to the lack of public relations of the academic journal activities leading to personnel’s insufficient understanding, lack of coordination between the journal committees and practitioners, limited budget, and lack of management flexibility caused by the bureaucratic system. 2) Factors contributing to the efficiency improvement in academic journal management at the Faculty of Humanities and Social Sciences were: a clear policy of public relations, adequate budget support, plan setting, and reporting as guidelines for the executives to support and improve academic journal operations. 3) The model of efficiency improvement in academic journal management of the Faculty of Humanities and Social Sciences showed that 3M and PDCA conceptual frameworks should be applied to academic journal management in order to increase operational efficiency and reduce processes. Moreover, the staff should understand their role in making decisions in accordance with research ethics. They should be supported in receiving training on research ethics, thaijo operational system, and the fast-track system.